Administrative Staffs’ Language Politeness During Academic Service Activities at Universitas Negeri Semarang - Madyaningtyas, Rina Sari; Rokhman, Fathur (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
Language politeness is important in the administration of administrative staff to the community. In practical life, many administrative staff do not have good and polite language skills. Many staff use language to communicate and provide services to the community as they like. This thing leads them to be judged that they are not able to provide good service to the community. Different speakers will have different code choices that impact on compliance and infringement of language politeness principles. The purpose of this study is to describe compliance with the principles of language politeness of the teaching staff in the academic environment at Universitas Negeri Semarang, including adherence to the principle of language politeness and factors influencing language politeness of educational staff in academic services at Universitas Negeri Semarang. The data was collected by using the listening method and tapping technique. Adherence to the principle of language administration politeness in the form of adherence to the thimble of inferiority, generosity, indulgence, approval, and conciliation.